Eosinophil plays a crucial role in intestinal mucositis induced by antineoplastic chemotherapy. Issue 3 (10th January 2022) - Arifa, Raquel D. N.; Brito, Camila B.; de Paula, Talles P.; Lima, Renata L.; Menezes‐Garcia, Zélia; Cassini‐Vieira, Puebla; Vilas Boas, Fabrício A.; Queiroz‐Junior, Celso M.; da Silva, Janine M.; da Silva, Tarcília A.; Barcelos, Lucíola S.; Fagundes, Caio T.; et al.
Abstract: Mucositis is a major clinical complication associated with cancer treatment and may limit the benefit of chemotherapy. Leukocytes and inflammatory mediators have been extensively associated with mucositis severity. However, the role of eosinophils in the pathophysiology of chemotherapy‐induced mucositis remains to be elucidated. Here, using GATA‐1‐deficient mice, we investigated the role of eosinophils in intestinal mucositis. There was marked accumulation of eosinophils in mice given irinotecan and eosinophil ablation inhibited intestinal mucositis. Treatment with Evasin‐4, a chemokine receptor antagonist, reduced the recruitment of eosinophils and decreased irinotecan‐induced mucositis. Importantly, Evasin‐4 did not interfere negatively with the antitumour effects of irinotecan. Evasin‐4 was of benefit for mice given high doses of irinotecan once Evasin‐4‐treated mice presented delayed mortality. Altogether, our findings suggest that Evasin‐4 may have significant mucosal‐protective effects in the context of antineoplastic chemotherapy and may, therefore, be useful in combination with anticancer treatment in cancer patients. Abstract : Evasin‐4 treatment decreases eosinophil influx and reduces intestinal mucositis and tumour growth: Irinotecan treatment induces cell damage in the gut. The intestinal damage induces an increase in CCL11 and CCL24 chemokines production and eosinophil activation and migration to the intestine. In addition, there is elevated production of cytokines and greater neutrophil influx into tissue. These events lead to intestinal damage.